Computational Analysis of the Flow Around an Exposed Wheel - Takeuchi, S. (Cranfield University, 2010)
This thesis presents an investigation of RANS and LES models for the isolated rotating exposed wheel with moving ground with the aim of analyzing the flow behavior and comparing the results in cost/quality context. This is motivated by general demand for the drag reduction in automobile industry. In addition the demand is even stronger from high-performance car competition where the tyre wake has a great impact on total performance such as lift force or aerodynamic stability aspect. Cont/d.